1997
DOI: 10.1159/000190166
|View full text |Cite
|
Sign up to set email alerts
|

Defect of Cell-Mediated Immune Response against Hepatitis B Virus; An Indication for Pathogenesis of Hepatitis-B-Virus-Associated Membranous Nephropathy

Abstract: To elucidate the questions of why not all patients with hepatitis B virus (HBV) infection develop HBV membranous nephropathy (HBVMN), we first measured serum HBe circulating immune complex (CIC) during the acute nephrotic phase of HBVMN and in HBV carriers. We found that the level of HBe CIC was low in the HBVMN patients and absent either in HBsAg+/ HBeAg+ patients without HBVMN or HBsAg+/HBeAg- asymptomatic carriers. Second, we needed to characterize the cellular immune response to HBV in patients with HBVMN.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The pathogenesis of HBV-associated GN is not fully understood [2,16]. The demonstration of HBsAg and HBeAg in the glomerular deposits suggests an immune complex mechanism leading to glomerular injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of HBV-associated GN is not fully understood [2,16]. The demonstration of HBsAg and HBeAg in the glomerular deposits suggests an immune complex mechanism leading to glomerular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that patients with HBVrelated MGN had an inadequate cellular immune response to HBeAg, causing defective clearance of virus particles and virus-infected cells [16]. Thus, the free form of HBeAg is filtered and deposited in the subepithelial zone of the GBM where it combines with antiHBe antibody, leading to HBV-related membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that a type-1 immune response was not predominant in idiopathic membranous nephropathy. In an analysis of PBMCs obtained from patients with hepatitis B virus (HBV) associated membranous nephropathy, IL-2 and IFN-γ production reportedly decreased more than that in HBV-infected patients without membranous nephropathy after in vitro stimulation with a hepatitis B core antigen [34]. Decreased IL-2 production may be a common phenomenon in membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HBV-associated membranous nephropathy, increased IL-10 production after in vitro stimulation with a hepatitis B core antigen was also reported [34]. IL-10 is produced by Th2 clones [35], and it suppresses cytokine production by Th1 cells and NK cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Lin et al [69]set out to elucidate why only some individuals with HBV infection developed MN. They did this by measuring serum HBeAg circulating immune complexes during the acute nephrotic phase of HBVMN and in the carrier stage of HBV.…”
Section: Pathogenesis Of Hbv-associated Nephropathymentioning
confidence: 99%